An outstanding antichlorine and antibacterial membrane with quaternary ammonium salts of alkenes via in situ polymerization for textile wastewater treatment - Liu, Chao; Guo, Yongqiang; Wei, Xinjing; Wang, Chao; Qu, Muchao; Schubert, Dirk W.; Zhang, Chunhua (Chemical Engineering Journal, 2019)
Developing an efficient and stable separation membrane material for textile water treatment is of considerable significance but challenging due to the limitation of chlorination degradation and bacterial fouling. To solve this problem, in this work, the amides groups in the polyamide structure were converted to imides by targeted grafted from diallyl dimethyl ammonium chloride (DADMAC) molecules. Consequently, chlorination degradation and bacterial fouling was markedly improved due to the reduction or elimination of N-H bonds and the increase of DADMAC grafting chains. Chlorine exposure experiment results showed that the salt rejection and water flux of modified membranes change less than that of the pristine membrane, and the surface morphology and chemical structure and basically remained unchanged. Meanwhile, the introduction of quaternary ammonium salt generated a hydrophilic and smooth membrane surface, thus improving the anti-fouling performance. In addition, with the advantage of an excellent antimicrobial activity, hardly any bacterial growth was observed even after 24 h culture, the membrane exhibits satisfactory stability in long-term textile water separation, which is considerable potential in the advanced wastewater treatment. The presented strategy on membrane preparation is believed to be a simple and effective method, which can also be widely used in other industrial wastewater treatment, such as medical wastewater, oilfield wastewater, etc.
CRIS-Team Scopus Importer:2019-12-03
Keywords: Anti-biofouling; Anti-chlorine; Membrane fouling; Reverse osmosis membrane; Wastewater treatment